Thermo-economic analyses of a Taiwanese combined CHP system fuelled with syngas from rice husk gasification. (15th January 2019) - Chang, C.T.; Costa, M.; La Villetta, M.; Macaluso, A.; Piazzullo, D.; Vanoli, L.
Abstract: A Combined Heat and Power (CHP) system fuelled with rice husk is analysed from the thermodynamic, exergetic and economic point of view. The system is based on a gasification process coupled with a rice drying system. The produced syngas is employed to power a Spark Ignition (SI) Internal Combustion Engine (ICE) working as an electric generator, while the jacket cooling water powers a bottoming Organic Rankine Cycle (ORC) to produce electricity for plant self-consumption. A parametric analysis is carried out to investigate thermodynamic performances by varying the gasifier Equivalent Ratio (ER): as the ER increases, the ICE produced power and combustion efficiency decrease, while the thermal efficiency increases. However, the system is always capable to produce power for self-consumption and the desiccant flow for drying. The characterization of the engine is then better assessed by means of a dedicated GT-Power engine model, optimized for syngas fuelling, revealing a power derating of the 30% with respect to the natural-gas feeding operation. Other main findings suggest that the global exergetic efficiency ranges between 10.6% and 8.5%, while the economic profitability, represented by the Simple Pay Back, Net Present Value and Profit Ratio, cannot be considered satisfactory due to the consistent investment cost. Highlights: Thermo-economic analysis of a CHP system fuelled with rice husk. Lower electric and higher thermal efficiency with increasing gasification ER. Numerical 1D ICE model reveals a power derating of 30% under syngas feeding. Total exergy efficiency is maximum for low gasification ER. The system is not economically satisfactory due to high investment costs.